An Analysis of Gender Based Legislation in Pakistan (1999-2013) - Munazzah Bukhari; Farzana Zaheer Syed; Huma Shah, (ASIAN Journal of International Peace & Security (AJIPS), 2021)
The role of women in Pakistan is not homogeneous since gender is correlated with numerous forms of social discrimination. As a result of unequal socioeconomic progress and the impact of tribal, feudal, and capitalistic social institutions on women's lives, women's positions vary drastically among professions, geographies, and the rural/urban divide. Gender based politics is a broad phrase with numerous connotations, particularly with reference to Pakistani society where gender discrimination is common. The state cannot remain indifferent and new legislation is urgently required on various aspects of women issues as the establishment of effective legal impediments can bring monetary prospects, employment, and social protection to the other half of the society. This study aimed to assess the role of women in politics in Pakistani society. A qualitative study method with explanatory analysis has been used to assess women's legislation in Pakistan from 1999 to 2013. It was determined that while great emphasis was placed on legislation, implementation and changing the mindset of the society, still remains a critical issue. This study assesses that Pakistan cannot progress until half of its population remains deprived and discriminated.